DEFINITION OF SOIL AREAS OF INDUSTRIAL ENTERPRISES POLUTANTS AND IDENTIFICATION OF THEIR ENVIRONMENTAL HAZARD - Іващенко, Т. Г.; Пушкарьова, І. Д. (Scientific Progress & Innovations, 2014)
This paper presents the results of qualitative and quantitative analysis of soil pollutants of the industrial enterprises stopped their activities, such as Saki State Chemical Plant. It was found that in samples of soil there are at least 26 pollutants, 5 of which belong to the first class of substances hazard. Concentration of pollutants were investigated and found that in some samples they exceed the maximum permissible concentration in 2-295 times. Article deals with environmental hazard factors of specific pollutants, in particular the impact on the human organism.